(untitled) (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2025)
Problem statement. An increase in air temperature and a decrease in precipitation does not have a negative impact on the yield of agricultural crops. There is an increase in the yield of grain and leguminous crops, sunflower, potatoes, vegetables, fruits and berries, which indicates their adaptive ability to climate change The purpose of the study is to establish the influence of weather conditions of the growing season on the formation of the productivity of pea varieties in the eastern part of the forest-steppe of Ukraine. Materials, methods, meteorological conditions. The study was conducted during 2006–2020 in the stationary crop rotation of the V. Ya. Yuryev Institute of Plant Production of the NAAS using the split-plot method according to generally accepted methods. The soil is deep slightly leached black soil with a granular structure. It is characterized by the following agrochemical indicators: humus content – 5.8%; pH – 5.8; hydrolytic acidity – 3.29 mg/eq. per 100 g of soil. Nutrient reserves in the control without fertilizers: nitrogen – 132 mg/kg, phosphorus – 104 mg/kg, potassium – 128 mg/kg; in the background with the use of mineral fertilizers (N30P30K30): nitrogen – 130-140 mg/kg, phosphorus – 180-200 mg/kg, potassium – 170-190 mg/kg of soil. Results. On average over the years of research (2006-2020), the deviation in the average daily temperature is plus 2.21 С. At the same time, there is a significant difference by month and year. A significant warming of the August-September period is noted, by 2.41-2.21 С, in other months the increase in air temperature is insignificant - 0.25 С in April, 0.70 С in May, 0.40 С in June and 0.64 С in July. Insufficient moisture was observed in 9 years (from 14.3 mm in 2007 to 168.1 mm in 2018), and excess - respectively in 8 years, with fluctuations from 41.1 mm in 2020 to 251.8 mm in 2011. On average, over the years of research, two months had less precipitation compared to multi-year values, these are April - 9.5% with a norm of 11.7% and July - 20.5 and 23.5%, respectively. In June, the amount of precipitation is above optimal indicators - 25.4 against 20.8%. In other months, the distribution of precipitation was close to the optimum. Conclusions. In April, 6 years out of 15 were with sufficient or excessive moisture, and in the others - with insufficient. In May - respectively in 8 years. June: 1 year sufficient amount (2008) and 6 years - excessive. In July - respectively - 1 and 5 years and in August - for the entire period of research, only 2 years were with excessive moisture, and all the others - with insufficient. According to the results of the correlation analysis of the influence of the precipitation distribution indicator on the level of crop yield, there is practically zero dependence between them on average for 15 years (2006-2020). At the same time, for the period 2006-2010, a high positive correlation was noted with April precipitation, r= 0.875-0.911 and a significant one with June humidity - r= 0.398-0.583. In 2011-2015, the distribution of precipitation in April, June and July had a negative impact on pea yield - r = from minus 0.452 to minus 0.366; r = -0.434-0.324 and r = -0.654-0.543, respectively. And in May, the correlation of factors was positive - r = 0.578-0.613. In 2016-2020, negative correlations were also noted in April and June - r = from minus 0.680 to minus 0.470 and r = -0.759-0.637, low correlation of indicators in May - r = 0.178-0.261.